"TO ME ITS [SIC] REAL LIFE": Secondary Victims of Homicide in Newer Media. Issue 3 (4th May 2017) - Yardley, Elizabeth; Wilson, David; Kennedy, Morag
Abstract: This article explores what happened when two people personally affected by a 1999 homicide participated in an online forum in which the homicide was being discussed. The two individuals in question were the younger brother of the victim and the elder brother of the man convicted of her murder. The case had been the subject of a 12-part audio podcast called Serial . An online forum—the Serial Subreddit — had been set up independently of the podcast and its producers as a space for listeners to discuss their views on the case. We analyzed the contributions of the two aforementioned individuals and the responses they received. We argue that new media spaces like the Serial Subreddit break down the traditional barriers between those personally affected by homicide and consumers of mediated representations of homicide. As such, they raise important questions for criminologists.